228k views
3 votes
How do you sovle this 5(x – 4) + 3x – 9x = 6 – (2x + 5) + 8x

User MSARKrish
by
6.4k points

1 Answer

4 votes

Answer: X=-3

Step 1) Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

5*(x-4)+3*x-9*x-(6-(2*x+5)+8*x)=0

Step 2) ((5 • (x - 4) + 3x) - 9x) - (6x + 1) = 0

Step 3) Pull out like factors : -7x - 21 = -7 • (x + 3)

Step 4) -7 • (x + 3) = 0

Step 5) Solve : -7 = 0 This equation has no solution.

A a non-zero constant never equals zero.

Step 6) Solve : x+3 = 0

Subtract 3 from both sides of the equation :

x = -3

Explanation:

User Electronick
by
6.0k points